2022
DOI: 10.5455/umj.20220616022839
|View full text |Cite
|
Sign up to set email alerts
|

Remnant Cholesterol and Leptin: Any Association in Normal Weight, Over Weight and Obese Individuals in South East Nigeria

Abstract: Introduction: Leptin circulating levels increase with weight gain and decrease with weight loss. The amount of leptin circulating in the body is proportional to an individual's fat. We investigated the association of leptin and remnant cholesterol in normal-weight, overweight and obese participants in southeast Nigeria. Materials and Methods: This is a cross-sectional random study. A total of 90 healthy obese, overweight, and normal-weight participants who met the inclusion criteria were randomly enrolled in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…RC has considered to be the main factor mediating the residual risk of major cardiovascular events [40,20,[41][42][43][44]. It has been stipulated that remnants cholesterol can be taken up directly by the microphages, thereby converting such cells into foam cells, which is the hallmark of atherosclerosis lesions and the hydrolysis of triglyceride in remnant particles at the endothelial surface or within the arterial intima may generate local inflammation [21,22]. However our findings showed that the risk of cardiovascular accidents by high levels of remnants cholesterol may not be sorely driven by BMI and level of fat tissues, this was observed in some overweight and normal weight individual with high level of remnant cholesterol, this was in accordance with the findings of Chinonso et al 2021.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RC has considered to be the main factor mediating the residual risk of major cardiovascular events [40,20,[41][42][43][44]. It has been stipulated that remnants cholesterol can be taken up directly by the microphages, thereby converting such cells into foam cells, which is the hallmark of atherosclerosis lesions and the hydrolysis of triglyceride in remnant particles at the endothelial surface or within the arterial intima may generate local inflammation [21,22]. However our findings showed that the risk of cardiovascular accidents by high levels of remnants cholesterol may not be sorely driven by BMI and level of fat tissues, this was observed in some overweight and normal weight individual with high level of remnant cholesterol, this was in accordance with the findings of Chinonso et al 2021.…”
Section: Discussionmentioning
confidence: 99%
“…"Remnant cholesterol has been suggested as a link from obesity to ischemic disease, i.e., a part of the elevation risk of ischemic heart disease observed in obese individuals was explain by higher remnant cholesterol concentration" [3,[19][20][21][22]. It is also known as remnant lipoprotein, which has been said to be very athrogenic lipoprotein and comprised primarily of very low density lipoprotein (VLDL), Intermediate density lipoprotein (IDL), and chylomicrons.…”
Section: Introductionmentioning
confidence: 99%